A Chalcogen-Bonding Cascade Switch for Planarizable Push-Pull Probes - Macchione, Mariano (Angew Chem Int Ed Engl, 2019)
Planarizable push-pull probes have been introduced to image physical forces in biology. However, the donors and acceptors needed to polarize mechanically planarized probes are incompatible with their twisted resting state. The objective of this study was to overcome this “flipper dilemma” with chalcogen-bonding cascade switches that turn on donors and acceptors only in response to mechanical planarization of the probe. This concept is explored by molecular dynamics simulations as well as chemical double-mutant cycle analysis. Cascade switched flipper probes turn out to excel with chemical stability, red shifts adding up to high significance, and focused mechanosensitivity. Most important, however, is the introduction of a new, general and fundamental concept that operates with non-trivial supramolecular chemistry, solves an important practical problem and opens much chemical space.